Landasan Filosofis Kekuatan Mengikatnya Kontrak - Ridwan Khairandy (Fakultas Hukum Universitas Islam Indonesia, 2011)
The problems of this research are: Firs of all, the influence of freedom of contract paradigm toward the binding forces of contact principle; secondly, the philosophical basis he binding forces of contact principle. To discus those problem, this research uses normative and comparative philosophical-juridical-normative approach. This research is a literary research, the legal matters are analyzed qualitatively using normative and juridical approach. This research concludes: First, under the influence of freedom of contract or freedom of will paradigm, the basis of system of law in justifying the basis of binding forces and performance of contract are obtained; Second, the sanctity of contract is one of the teaching followed by classic theory of contract law as a direct result of freedom of contract. The philosophical basis of binding forces in Islamic Law is derived directly from Al Quran.